UPAYA ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR DI ERA DIGITAL - Lia Ananta; Nila Hani Awalia (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
In the rapidly evolving digital age, the role of parents in supporting their children's learning process is increasingly crucial. This study aims to explore the efforts made by parents in facilitating their children's learning amidst the advancements in digital technology. The research method employed is a literature review to gather information from various reliable sources. The findings indicate that parents face new challenges in managing technology use at home and ensuring their children can utilize it productively. Common efforts made by parents include limiting screen time, guiding in selecting appropriate digital content, and providing positive support for online learning. However, there is still a need for a deeper understanding of how parents can effectively integrate digital technology into their children's learning without neglecting other essential aspects of their development. This research offers valuable insights for parents, educators, and practitioners in designing strategies to support children's learning in this digital era.